دراسة تطور التحرير المصرفي في الدول النامية دراسة حالة الجزائر، تونس، المغرب و الاردن - سنوسي, قويدر; زناخي, فوزية (جامعة الوادي - University of Eloued, 2018)
This paper aims to examine the banking liberalization path in developing countries, with a focus on the following countries Algeria, Tunisia, Morocco and Jordan. After analyzing the data obtained from the World Bank and the Arab Monetary Fund during the period 1990 to 2015, the results showed that Jordan had the highest proportion of cash supply, followed by Morocco, Tunisia and Algeria, this can be explained due to the evolution of the banking system in these countries; the orientated private sector credit index results to Algeria in 1990, which represented from this index exceeds 55%, but quickly declined during the following years, while Morocco, Tunisia, and Jordan knew continuous growth. The financial sector has achieved in the four countries expand in size and activity, especially Jordan, while monetary policy has been the year 2013 was characterized by a move towards expansion and is reflected in the direction of domestic liquidity growth at the country level rate, where domestic liquidity at a rate of 12.90% grew during the year 2013 compared to 11.50% in 2012. For Algeria, the development indicators financial reflect the degree of improvement, which remains inadequate compared to what witnessed in the vicinity of its financial system developments and transformations, which calls for more work on the rehabilitation and development of the structure and performance of this system.
study of the evolution of banking liberalization in developing countries The case Study of Algeria, Tunisia, Morocco and Jordan
مقال
Keywords: التحرير المصرفي، القطاع المصرفي، التسييل النقدي، الائتمان الخاص; liberation banking, the banking sector, the monetary liquefaction, private credit